2009
DOI: 10.1073/pnas.0908274106
|View full text |Cite|
|
Sign up to set email alerts
|

Highly specialized microbial diversity in hyper-arid polar desert

Abstract: The McMurdo Dry Valleys in Antarctica are a cold hyperarid polar desert that present extreme challenges to life. Here, we report a culture-independent survey of multidomain microbial biodiversity in McKelvey Valley, a pristine example of the coldest desert on Earth. We demonstrate that life has adapted to form highly-specialized communities in distinct lithic niches occurring concomitantly within this terrain. Endoliths and chasmoliths in sandstone displayed greatest diversity, whereas soil was relatively depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
414
7
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 350 publications
(460 citation statements)
references
References 53 publications
36
414
7
3
Order By: Relevance
“…Morphological examination of phototrophic microbes has been useful in comparison of Arctic and Antarctic cryoconite holes (Porazinska et al, 2004;Stibal et al, 2006), but the limited range of observable morphology hinders the application of this approach to most non-photosynthetic bacteria. Although archaea have been reported from several peri-glacial habitats (Sjöling and Cowan, 2003;Nicol et al, 2006), other PCR-based investigations have also failed to detect their presence (Pointing et al, 2009); (Supplementary Data S1). Further study using PCR-independent approaches (for example, phospholipid ether lipid analysis; Gattinger et al, 2003) could usefully be applied to provide a definitive determination of the occurrence of archaea within cryoconites.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological examination of phototrophic microbes has been useful in comparison of Arctic and Antarctic cryoconite holes (Porazinska et al, 2004;Stibal et al, 2006), but the limited range of observable morphology hinders the application of this approach to most non-photosynthetic bacteria. Although archaea have been reported from several peri-glacial habitats (Sjöling and Cowan, 2003;Nicol et al, 2006), other PCR-based investigations have also failed to detect their presence (Pointing et al, 2009); (Supplementary Data S1). Further study using PCR-independent approaches (for example, phospholipid ether lipid analysis; Gattinger et al, 2003) could usefully be applied to provide a definitive determination of the occurrence of archaea within cryoconites.…”
Section: Discussionmentioning
confidence: 99%
“…Lithic communities in McKelvey Valley (Pointing et al 2009) and the Miers, Marshall, and Garwood Valleys (Khan et al 2011) were found to be distinct from surrounding soil communities, suggesting substantial dissemination of biomass to the local environment is restricted. Similarly, while the presence of an animal carcass at a site may drastically alter the physicochemical parameters and bacterial community composition of the soil, the effects have been found to be restricted to the immediate vicinity of the augmentation (Tiao et al 2012).…”
Section: Desert Soilsmentioning
confidence: 99%
“…Devoid of vascular plant life [8][9][10] , the Dry Valley ecosystem supports only a handful of microscopic invertebrate, lichen and moss species 9,10 . However, the bulk of Dry Valley biodiversity and biomass consists of edaphic bacteria 8,11,12 , as few other organisms can endure the region's extreme temperature and light regimes, high soil salt concentrations, near-negligible levels of organic C and N, and scarcity of liquid water 10,12 . It has been suggested that these soil microbial communities are principally sustained and structured by the location and distribution of legacy C sources in the form of ancient lake sediments [13][14][15][16] .…”
mentioning
confidence: 99%